O corpo-arte em devir : a performance artística como contradispositivo filosófico de controle dos corpos - Silva, Bruno Anderson Souza da (2023)
In this study, we base our analysis on the premise that artistic performance stands in opposition to necropolitics and biopolitics, which, in turn, seek to discipline bodies, since artistic performance is seen as yielding undisciplined bodies. In other words, through artistic performance, one could potentially engender micropolitics or something in the vicinity of the creation of a body without organs (BwO), as proposed by Antonin Artaud in his final performance, titled "Pour en finir avec le jugement de Dieu" (1947) (and further elaborated upon by Gilles Deleuze and Félix Guattari), as we will explore in our study. Among the objectives of this research, we seek to comprehend the contemporary processes of subjectivization and the struggles against the systematic forms of domination and body discipline. The aim is to ascertain if artistic experimentation can give rise to a becoming-body, which translates into an event capable of augmenting the power to act of bodies and forging escape routes to liberation. Finally, we seek to address the question of whether there is something within artistic experiments that could bring forth a becoming-body, i.e., an event generated from the encounter and disruption of bodies, capable of increasing their power to act; and how this event can operate an unforeseen opening in culture and art, serving as a form of philosophical resistance to the politics of body control (biopolitics and necropolitics).